Intensi Kewirausahaan : Studi pada Faktor Individual, Situasional, dan Perbedaan Gender - Audrey Jocelyn Hertanto; Frangky Slamet (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2020)
The purpose of this research is to determine the effect of individual factors and situational factors, as well as gender difference as the moderating variable, on the entrepreneurial intention among vocational high school students in West Jakarta. The number of samples use in this study is50 respondents of vocational high school students in West Jakarta and use purposive sampling technique for choosing the respondents. This research uses Statistical Package for the Social Science (SPSS) software version 17.0 to analyze the data collected. The results of this research indicates that individual factors, situational factors and gender difference have no significant impact on entrepreneurial intention. However, individual factors demonstrate greater effect on entrepreneurial intention than situational factors. Penelitian ini bertujuan untuk mengetahui pengaruh faktor individual, situasional terhadap intensi kewirausahaan dengan perbedaan gender sebagai variabel moderasi pada siswa/I SMK di Jakarta Barat. Sampel yang digunakan dalam penelitian ini sebanyak 50 responden yang merupakan siswa/I SMK di daerah Jakarta Barat dan teknik pemilihan sampel yang digunakan adalah purposive sampling. Untuk metode analisis data pada penelitian ini menggunakan softwareStatistical Package for the Social Science (SPSS) versi 17.0. Hasil penelitian ini menunjukkan bahwa faktor individual, faktor situasional, dan perbedaan gender tidak memiliki pengaruh terhadap intensi kewirausahaan. Namun, faktor individual memiliki pengaruh yang lebih kuat daripada faktor situasional terhadap intensi kewirausahaan.